Analysis of Needs For Using Android-Based KPSP Applications In Monitoring The Growth of Together - Nuraini, Indria; Hasiana, Isabella; Gamas, Nabila Sayangbati (Universitas STRADA Indonesia, 2021)
Background: The development process occurs simultaneously with growth, so that every growth is accompanied by a change in function. Development is the result of the interaction of the maturity of the central nervous system with the organs it affects. The development of the early phase in the form of cognitive, motor, emotional, social, and language functional abilities, is a determinant of the development of the next phase. If there is a deficiency in one aspect of development, it can affect other aspects, so there is a need for early detection of toddler growth and development.Purpose: This study aimed to find out the need for KPSP applications in monitoring the growth and development of toddlers.Methods: This research uses a descriptive-analytic design, cross-sectional approach. The population of this study amounted to 36 respondents, with a purposive sampling technique. The research site is in the Surabaya area by distributing questionnaires in the form of Google Form. Analyze data with Descriptive Analysis.Results: The results of this study stated that before the pandemic monitoring of toddler growth and development was carried out at the Posyandu using the KIA Handbook Instrument/Tool, while during the pandemic monitoring of toddler growth and development could not be carried out directly because of a policy. In this regard, respondents need an instrument/tool that can be used for independent monitoring of growth and development.Conclusion: Monitoring the growth and development of toddlers during the pandemic by utilizing technological advances and being up to date